Fascia Iliaca Blocks Performed in the Emergency Department Decrease Opioid Consumption and Length of Stay in Patients with Hip Fracture. Issue 3 (March 2022) - Kolodychuk, Nicholas; Krebs, John Collin; Stenberg, Robert; Talmage, Lance; Meehan, Anita; DiNicola, Nicholas
Abstract : Objectives: To examine the impact of fascia iliaca (FI) blocks performed in the emergency department on patients with hip fracture on opioid consumption, length of stay, and readmission rate. Design: Prospective cohort study. Setting: Community-based Level 1 trauma center. Patients/Participants: Ninety-eight patients with isolated femoral neck, intertrochanteric, and subtrochanteric femur fractures (OTA/AO 31-A and 31-B) presenting from January 1, 2020, to June 30, 2020. Intervention: Ultrasound-guided FI compartment block using 40 mL of 0.25% bupivacaine. Main Outcome Measurements: Opioid consumption, length of stay, discharge disposition, and 30-day readmission rate. Results: Thirty-three patients had contraindication to FI block. Thirty-nine of 65 patients (60%) without contraindications to undergoing FIB received FI block. Mean age, body mass index, fracture type, and surgical procedure were similar between patients undergoing FIB and not receiving FIB. The FIB group had significantly lower opioid consumption preoperatively [17.4 vs. 32.0 morphine milliequivalents (MMEs)], postoperatively (37.1 vs. 85.5 MMEs), over total hospital stay (54.5 vs. 117.5 MMEs), and mean opioid consumption per day of hospital stay (13.3 vs. 24.0 MMEs). Patients in the FIB group had shorter length of stay compared with the control group (4.3 vs. 5.2 days). There was no significant difference in discharge disposition destination between groups. No patients reported complications of FI block. Conclusions: Undergoing FI block in the emergency department was associated with decreased opioid consumption, decreased length of stay, and decreased hospital readmission within 30 days of hip fracture. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.